Amino Acids, Peptides and Proteins [Vol.42] - Maxim, Ryadnov [Ed.]; Hudecz, Ferenc [Ed.] (Uk : CRC Press, 2018)
Amino Acids, Peptides and Proteins comprises a comprehensive and critical review of significant developments at the biology and chemistry interface. Compiled by leading researchers in their subject, this volume incorporates current trends and emerging areas in topics such as magnetic resonance studies of membrane active peptides, proteins and peptides for the diagnosis and therapy of Leishmania donovani parasite infections and advances in the design of ligands interacting with proteases causing infectious respiratory syndrome. Appealing broadly to researchers in academia and industry, it will be of great benefit to any researcher wanting a succinct reference on developments in this area now and looking to the future.
Keywords: Organic Chemistry -- Acids : Amino Acids -- Peptides